A ação relaxante de novos derivados N-sulfonilidrazônicos do LASSBio-448, inibidores de PDE4, em um modelo de asma alérgica em cobaias: caracterização funcional do mecanismo relaxante do LASSBio-1847 - Martins, Italo Rossi Roseno (2016)
Asthma is a condition characterized by reversible chronic inflammation and hyper responsiveness of airways, with a pharmacotherapy well established. However, due to asthma heterogeneity, some patients did not respond to treatment. So, trying to contribute in the development of new candidates to antiasthmatic drugs, we decided to assess a possible relaxant action of PDE4 inhibitors N-sulfonilhidrazonic derivatives (LASSBio-448, -1624, -1832, -1846, -1847, -1848, -1849, -1850 and -1851) in functional model of trachea from non-asthmatic and asthmatic guinea pigs, as well as to characterize the action mechanism of the most promising derivative. All experimental protocols were approved by CEUA/UFPB (certificate 0610/11). Initially, we realize the implementation and standardization of a guinea pig asthma model using ovalbumin (OVA) as sensitizer agent, and it was histologically observed morphological changes associated to asthma, as hypertrophy of the smooth muscle layer, inflammatory cells infiltration and vascular abnormalities. Moreover, rings from sensitized guinea pig trachea showed to be responsive to OVA, differently to the non-sensitized animals. Functionally, the contractile agonist CCh presented efficacy and potency similar between non asthmatic and asthmatic animals, differently histamine demonstrated to be equipotent between the animals, but with a higher efficacy in the asthmatic guinea pigs. In turn, the relaxant agonist aminophylline and isoprenaline presented similar potency and efficacy in both non asthmatic and asthmatic animals. Generally, in the step of pharmacological screening of N-sulfonilhidrazonic derivatives, they presented a equipotent relaxant action and independent of relaxing factors derived from epithelium in both animals groups, with exception of LASSBio-1850 that presented a low efficacy (< 50%) and LASSBio-1847 with a 4 fold higher potency on asthmatic guinea pigs. Among the derivatives evaluated, LASSBio-1632, -1846 and -1847 were the one with higher pharmacological potency on asthmatic animals, and LASSBio-1847 was the most promising and selected to the step of characterization of action mechanism on non-asthmatic and asthmatic guinea pig. Such as LASSBio-1847 was synthetized as a PDE4 inhibitor, an enzyme that hydrolyze cAMP, and the β2 -adrenergic receptors are responsible to initiate the signaling involved to cAMP production on airway smooth muscle, we used propranolol, a β2-adrenergic non-selective blocker, to assess the participation of these receptors. So, we observed that the LASSBio-1847 relaxant curve was shifted showing the involvement of β2 -adrenergic receptors in both animal groups. Since these receptors lead to adenylyl cyclase (AC) activation, we decided to investigate its participation in the LASSBio-1847 relaxant effect. Therefore, we used forskolin, an AC activator, and evidenced that the relaxant curve was 54- and 4-fold shifted to the left in non-asthmatic and asthmatic animals, respectively, indicating that LASSBio-1847 could be acting in a synergic or facilitate the AC activation. β2-adrenergic receptors/AC activation lead to cAMP production that is regulated be its hydrolyzes by PDEs. To evaluate the contribution of these enzymes, we used aminophylline, a non-selective inhibitor of PDEs, and concentration-response curve to aminophylline was shifted to the left in the presence of LASSBio-1847 with gain in the potency around 147- and 4-fold in non-asthmatic and asthmatic animals, respectively, suggesting that the derivative acts by a possible PDE inhibition. The effector the β2-adrenergic receptors/AC/cAMP pathway is PKA, so to confirm its positive modulation by LASSbio-1847, we used H-89, a PKA inhibitor, observed a reduction in the relaxant potency of the derivative, confirming the modulation of this pathway. Until now, all finding have indicated a possible increase in [cAMP]c and to confirm this hypothesis it was carried out the measurement of tissue levels of cAMP by ELISA, that demonstrated that LASSBio-1847 indeed increase the [cAMP]c in a similar magnitude to rolipram, a selective PDE4 inhibitor, in both animals. Thus, it was established the implantation of the guinea pig asthma model, as well as the evaluated N-sulfonilhidrazonic derivatives presented relaxant activity on guinea pig trachea in both non asthmatic and asthmatic animals in an epithelium independent manner, and LASSBio-1847 showed to be one of the most promising compounds in relax this organ by activation of β2-adrenergic receptors/AC/cAMP pathway and inhibit the PDEs, culminating to elevation of [cAMP]c.